2017
DOI: 10.1089/cyber.2016.0322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Playing Exergames on Mood States: A Randomized Controlled Trial

Abstract: To examine how playing exergames impacts the mood states of university students and staff, and whether such an impact depends on gender and players' previous exercise time. This study was designed as a randomized controlled trial. It enrolled 337 participants and randomly assigned them to an intervention group (n = 168) or a control group (n = 167). A 2-week exergame program was designed for the participants in the intervention group. They were required to play exergames for 30 consecutive minutes each week fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…This suggests meaningful increases of older people’s feelings of being active and vigorous and benefits in emotional well-being after exergaming. Our findings agree with the premise that exergaming may induce positive mood states in users [ 105 , 106 ].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests meaningful increases of older people’s feelings of being active and vigorous and benefits in emotional well-being after exergaming. Our findings agree with the premise that exergaming may induce positive mood states in users [ 105 , 106 ].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests meaningful increases of older people's feelings of being active and vigorous and bene ts in emotional well-being after exergaming. Our ndings agree with the premise that exergaming may induce positive mood states in users [105,106].…”
Section: Painsupporting
confidence: 90%
“…Research has shown that exercise leads to a range of benefits for patients in relation to obesity, [ 18 ] cardiovascular disease, musculoskeletal health, [ 19 , 20 ] type 2 diabetes, 20 inflammatory biomarkers, [ 21 , 22 ] cancer, [ 23 ] wound healing, [ 24 ] and emotional state. [ 25 ] Several studies have investigated the relationship between physical activity and psoriasis, and some of these studies have found contradictory data. [ 26 30 ] Some scholars believe that physical activity is likely to aggravate the severity of psoriasis, while others believe that psoriasis is likely to improve following a course of voluntary exercise.…”
Section: Introductionmentioning
confidence: 99%